Eine Technologie für das durchgängige und automatisierte Testen eingebetteter Software - Fischer, Till (KIT Scientific Publishing, 2017)
Embedded software demands intensive testing of functional and non-functional requirements. Automation of such tests is performed with different technologies. Source-code level tests require specialized unit-testing tools. Tests of the high-level behavior of control systems follow the model-, software- and hardware-in-the-loop approach. This work studies the integration of such system-level and source-code level tests. The focus lies on a new programming language to implement test cases.